Fungsi, Perencanaan dan Pengawasan Serta Perbedaan Manajamen Bisnis Perkebunan Maupun Analisa Masalah yang Timbul dalam Manjamen Perkebunan - Chandara Putri; Dewi Sitohang; Riki Siringo-Ringo; Satrio Ananto; Saleh Sitompul; Putra Sinulingga; Marzuti Isra; Suhendri Suhendri (Lembaga Pengembangan Kinerja Dosen, 2026)
Business management in oil palm plantations is a process of managing resources to achieve optimal productivity within an industry that is highly dependent on natural factors. This article conducts a literature review on the concept and functions of plantation business management, its differences from business management in other sectors, as well as planning and control aspects based on Good Agricultural Practices (GAP). Using a review approach of recent scholarly journals, the article identifies key challenges, including dependence on natural conditions, long production cycles, and environmental considerations, and presents solutions grounded in scientific evidence. The findings indicate that strategic planning and digitally based monitoring can enhance efficiency and sustainability in oil palm plantations.